MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENERAPKAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA APLIKASI CANVA (PENELITIAN TINDAKAN KELAS PADA MATERI GOTONG ROYONG MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV UPT SDN 019 MUARA UWAI) - Dora Shinta Harianti; Mufarizuddin; Sumianto; Lusi Marleni; Adityawarman Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to enhance the learning motivation of fourth-grade students at UPT SDN 019 Muara Uwai in the subject of Pancasila Education through the implementation of the Contextual Teaching and Learning model assisted by the Canva application. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of two meetings. Research instruments included teaching modules, observation sheets for teacher and student activities, and a learning motivation questionnaire. The results showed an increase in students' learning motivation from a pre-action rate of 46.6%, to 63.33% in the first cycle, and reaching 83.3% in the second cycle. This improvement was evident in students’ active participation in discussions, presentations, and enthusiasm for using Canva’s visual media. The implementation of the Contextual Teaching and Learning model assisted by Canva made learning more engaging, contextual, and relevant to students’ lives, positively impacting both motivation and learning outcomes. The study recommends the use of the Contextual Teaching and Learning model and interactive digital media such as Canva as innovative alternatives in Pancasila Education at the elementary school level.